The Effect of White Turmeric Extract (Curcuma Zedoaria) and Lactobacillus sp Herbal Mixture as Feed Additive on Animal Productivity - Yayuk Astuti; Mega Bara Cahyantari (Journal of Science & Science Education, 2020)
This study was conducted to determine the effect of herbal white turmeric extract (Curcuma zedoaria) with Lactobaccilus sp on the productivity of livestock. The test subjects within this study are 50 broiler chickens aged 0 days which were divided equally into two observation groups, namely the control group (A) and the treated group (B). The treatments are carried out as follows: A = no animal herbal mixture was added into the drinking water; B = drinking water was added with herbal mixture. Average body weight of the chickens were (A) 460 g and (B) 484 g, the feed conversion ratio values for chicken aged 6 and 13 days respectively are 0.696 (A); 0.644 (B) and 1.25 (A); 1.18 (B), while the performance index value (IP) of broiler chickens aged 6 and 13 days were 335 (A); 390 (B) and 272 (A); 315 (B), consecutively. In this study the addition of herb as feed additives into broiler chicken drinking water can increase the average body weight of the treatment group compared to the control group, the treatment group has a lower FCR value indicating good feed efficiency and IP values ​​above 300 implying good breeding process.